The effect of 8-week combined balance and plyometric training on change of direction performance of young badminton players - Cheng Guo; Mian Xu (Scientific Reports)
Abstract The purpose of this study was to examine the effect of an 8-week combined balance and plyometric training on the Change of Direction (COD) performance of young badminton players. The study hypothesized that 8 weeks of combined training would improve COD performance in young badminton players. A total of 48 young male badminton players were recruited and randomly assigned to two groups: balance + plyometric training (BP; n = 24) and plyometric training alone (PL; n = 24). All the participants completed a 2-week familiarization process before the intervention. Both groups underwent their respective training sessions three times per week. Performance was assessed using the modified Southeast Missouri (SEMO) Test, modified T-Test, Hexagon Test, and Lower Extremity Injury Risk Test. The results showed significant improvements in COD performance for both groups, with the BP group showing superior performance in the modified T-test and Hexagon Test compared with that shown by the PL group. Specifically, the BP group had significant time and interaction effects on the T-Test (p < 0.001, partial η2 = 0.18) and Hexagon Test (p < 0.001, partial η2 = 0.15) scores. No significant time effect (p = 0.345) and interaction (p = 0.551) were observed for the SEMO test. Additionally, the BP group showed greater improvements in dynamic postural stability index (DPSI)-DF (p < 0.01, partial η2 = 0.69), DPSI-NF (p < 0.01, partial η2 = 0.27), and DPSI-NL (p < 0.01, partial η2 = 0.30). Significant time and interaction effects were also observed for LSI (Limb symmetry index)-3 (p < 0.01, partial η2 = 0.18) and LSI-6 (p < 0.01, partial η2 = 0.54). The 8-week BP program compared with PL significantly enhanced the COD performance and reduced the lower limb injury risk in young badminton players. The BP regimen proved more effective than the PL in improving dynamic balance, neuromuscular control, and stability, suggesting that integrating balance training with plyometric exercises is superior for optimizing performance and preventing injuries in this athletic population.